KEDUDUKAN PEMILIK MANFAAT (BENEFICIAL OWNERSHIP) DALAM PENERAPAN PRINSIP MENGENALI PEMILIK MANFAAT PADA SUATU PENDIRIAN BADAN HUKUM YAYASAN - Magfirah Hamsah; Abdul Maasba Magassing; Muhammad Basri (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2021)
Application of the Principles of Recognizing Beneficial Ownership in Foundations Based on Notary Deeds, guided by Mr. Abdul Maasba Magassing as the main mentor and Mr. Muhammad Basri as the co-mentor. This study aims to examine and analyze the position of beneficial ownership in the application of the principle of recognizing beneficial owners in a foundation legal entity establishment, as well as to study and analyze the role of the notary regarding the obligation to disclose beneficial ownership in the establishment of a foundation. This type of research is normative supported by primary and secondary data. The data analysis used is qualitative with a theoretical basis. Furthermore, the data is presented descriptively. This type of research is normative, supported by primary and secondary data. The data analysis used is qualitative with a theoretical basis. Furthermore, the data is presented descriptivelyThe results showed that the implementation of the principle of recognizing beneficial owners in foundations has not been fully implemented. This is due to the absence of strict sanctions for foundations that do not report beneficial owners or do not update information on beneficial owners to relevant regulators and the category of beneficial owners in foundations of 25% (twenty five percent) is still minimal. In addition, a notary as a party reporting in the prevention and eradication of the crime of money laundering cannot be the same as the reporting party for financial service institutions or other agencies. To implement Government Regulation No. 43 of 2015, the reporting party must be fully protected by law enforcement officials.